Finite Element Analysis New Trends and Developments - Ebrahimi, Farzad (IntechOpen, 2012)
In the past few decades, the Finite Element Method (FEM) has been developed into a key indispensable technology in the modeling and simulation of various engineering systems. The present book reports on the state of the art research and development findings on this very broad matter through original and innovative research studies exhibiting various investigation directions of FEM in electrical, civil, materials and biomedical engineering. This book is a result of contributions of experts from international scientific community working in different aspects of FEM. The text is addressed not only to researchers, but also to professional engineers, students and other experts in a variety of disciplines, both academic and industrial seeking to gain a better understanding of what has been done in the field recently, and what kind of open problems are in this area.